Analysis of TPS Learning (Think, Pair, Share) Based on Differentiation Process on Students' Numeration Abilities - Cahyani, Aulia Febi Dwi; Nuriyatin, Siti; Kusumawati, Intan Bigita (Universitas Teknokrat Indonesia, 2025)
Numeracy is a skiil in applying number concepts, artihmetic operations skiils and solving mathematical problems in various contexts related to real life. So cooperative learning type TPS (Think, Pair, Share) based on process differentiation is learning that is able to adapt to the needs and level of understanding of each student and has the potential to improve students’ numeracy abilities. This research aims to find out if there is a difference in increasing the numeracy skills of the low group, the middle group and the high group before and after treatment and aims to evaluate students’ numeracy abilities in cooperative learning type TPS (Think, Pair, Share) based on process differentiation. The research method used is One Group Pretest-posttest. The subjects in this research were students in class VIII-B of SMP Plus Arroudhoh with a total of 32 students. The data collection techique uses a pretest-posttest of data content and uncertainty in the event material, involving a total of 6 descriptive questions. Based on the research results, there were differences in the increase in numeracy skills of the low group, middle group, and high group before and after treathment. This is based on the results of the One-Way Anova test analysis of the N-Gain Score of the pretest-posttest data for the three group showing that the Sig. equal to 0.004< 0.05 then H0 s rejected. As well as the average posttest score for each group, it can be seen that the indicator most mastered by students is the 1st indicator and the indicator less mastered by students is the 3rd indicator.